Pentingnya Mendeteksi Hiperammonia Transien pada Bayi Baru Lahir (Transient Hyperammonemia of the Newborn/THAN) - Juliani Dewi (MEDICINUS, 2026)
Ammonia is a byproduct of nitrogen metabolism. In healthy individuals, ammonia is transported and metabolized under tight regulation to maintain low plasma concentrations. Increased ammonia production or insufficient ammonia detoxificationmay cause hyperammonemia. Transient hyperammonemia of the newborn (THAN) is often underdiagnosed, although it may lead to coma and death, particularly in premature infants. Acute hyperammonemia is an emergency condition thatmay cause cerebral edema, seizures, coma, severe neurological damage, and death. Ammonia levels can be measured using either an automated analyzer or dry slide. With early detection and prompt, appropriate treatment, the prognosis ofTHAN is excellent, without neurological sequelae.